2022
DOI: 10.1039/d1qo01753e
|View full text |Cite
|
Sign up to set email alerts
|

Simple inorganic base promoted polycyclic construction using mucohalic acid as a C3 synthon: synthesis and AIE probe application of benzo[4,5]imidazo[1,2-a]pyridines

Abstract: A transition metal-free and efficient synthesis of fused azapolycycles via multicomponent reaction has been developed from mucohalic acid as C3 synthon. The reaction promoted by simple inorganic base K2CO3 gives...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…These results indicate that the reaction might not undergo via a radical pathway. Thus, based on the results presented above and our previous works on the chemistry of mucohalic acids, [21,[30][31][32][33]47] a possible mechanism is proposed for the model reaction, which is shown as Scheme 5. Initially, mucobromic acid 2 a is isomerized into the ring-opened form 2 a'.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These results indicate that the reaction might not undergo via a radical pathway. Thus, based on the results presented above and our previous works on the chemistry of mucohalic acids, [21,[30][31][32][33]47] a possible mechanism is proposed for the model reaction, which is shown as Scheme 5. Initially, mucobromic acid 2 a is isomerized into the ring-opened form 2 a'.…”
Section: Resultsmentioning
confidence: 98%
“…Previously, we reported that, acting as C 3 synthons, mucohalic acids can be applied to obtain the polyheterocyclic compounds with the property of aggregation-induced emission (AIE). [30] In fact, owing to their multi-reactive sites, mucohalic acids also usually act as the unique C 4 synthons. [31][32][33] Herein, we disclosed the cyclization of aromatic sulfonyl hydrazides and mucohalic acids as C 4 synthons under the promotion of ptoluenesulfonic acid (p-TSA, Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…After decarboxylation, Michael addition of another benzimidazole is performed. With the aid of the base, a dehydrohalogenation reaction proceeds and the desired product is obtained by cyclization (Supplementary Material S23) (Yang et al, 2022). Via Michael addition, other NH-containing heterocyclic nucleophiles can also be introduced to the system.…”
Section: Nitrogen Heterocyclesmentioning
confidence: 99%
“…[29,31] Recently, Tang's group reported a decarboxylative multicomponent polymerization of p-phenylenediacetic acid, S 8 and aromatic diamines to convert S 8 into functional polythioamides with great structural diversity, large molecular weights and excellent yields. [32] Inspired by this, in the combination with our previous researches on the use of cheap inorganic bases in organic synthesis, [39,40] we utilized the decarboxylation of 2-halophenylacetic acids with a ring-forming reaction site in the presence of aromatic amines and S 8 as reactants to construct cyclic disulfide compounds. [25,32,[35][36][37][38] Because there are many kinds of aromatic amines as well, [41,42] our new three-component reaction can be used as a new method for the synthesis of benzene disulfide heterocyclic compounds with high efficiency, green and easily available starting materials.…”
Section: Scheme 2 Control Experimentsmentioning
confidence: 99%